Customer Satisfaction Analysis of ShopeeFood Service Quality using E-Servqual Method and Importance-Performance Analysis - Yanti, Rahma; Megawati, Megawati; Zarnelly, Zarnelly; Saputra, Eki; Marsal, Arif (Sistemasi: Jurnal Sistem Informasi, 2025)
ShopeeFood was launched in April 2020. However, since its initial release, traffic to ShopeeFood services did not immediately perform well, as the platform had to compete with major players like GoFood and GrabFood, which are already well-known among the public. Numerous negative customer reviews about ShopeeFood indicate that customer satisfaction with the company's performance remains low. To measure the level of customer satisfaction, this study employed the E-Service Quality (E-Servqual) and Importance-Performance Analysis (IPA) methods. The results of the study show that, on average, the seven dimensions of E-Servqual measured exhibit a gap, with the average gap being negative. The highest gap was found in the "Responsiveness" dimension (-0.32), while the lowest gap was in the "Efficiency" dimension (-0.01). These findings indicate a discrepancy between customer expectations and satisfaction, suggesting that ShopeeFood's services are perceived as less satisfactory by its users. Data analysis revealed that the Importance-Performance Analysis (IPA) matrix for ShopeeFood's service quality highlights several attributes as top priorities for improvement. These attributes, identified through the Cartesian diagram of the Importance-Performance Analysis, fall under Quadrant I, specifically R11, RE16, and C19.